2018
DOI: 10.1371/journal.pone.0195839
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of cow milk naturally enriched with polyunsaturated fatty acids and polyphenols in diets for diabetic rats

Abstract: The increasing incidence of diabetes mellitus is becoming a serious threat to human health in various parts of the world. Studies with dairy products have shown a potential beneficial effect against diabetes. This experiment evaluated the supplementation of milk naturally enriched with polyunsaturated fatty acids (PUFA) and polyphenols in rats with streptozotocin-induced diabetes. Forty male 28-day-old Wistar rats were distributed in four experimental treatments of diabetic animals (streptozotocin induction) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…It has been shown that PUFA are deleterious to microorganisms [ 11 ] and mainly affect those that degrade the cell wall, since these FA have a cytotoxic effect [ 35 ]. The reduction in the total digestibility of NDF and ADF differs from the findings of Yoshimura et al [ 36 ], who added the same amount of flaxseed oil into the diets of dairy cows and did not have differences in these parameters.…”
Section: Discussioncontrasting
confidence: 93%
“…It has been shown that PUFA are deleterious to microorganisms [ 11 ] and mainly affect those that degrade the cell wall, since these FA have a cytotoxic effect [ 35 ]. The reduction in the total digestibility of NDF and ADF differs from the findings of Yoshimura et al [ 36 ], who added the same amount of flaxseed oil into the diets of dairy cows and did not have differences in these parameters.…”
Section: Discussioncontrasting
confidence: 93%
“…Human studies have shown the benefits of naturally enriched products on atherosclerotic markers and low‐density lipoprotein (LDL) levels in various studies such as Wang et al () and Pintus et al (). Yoshimura et al () performed a laboratory experiment to evaluate their effect on patients suffering from diabetes. Implementing oilseed as a natural enrichment to the typical diet of dairy ewes is a common method for improving milk quality by increasing the UFA content, both for pasture‐based diets and for farm‐rationed diets (Cabiddu et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Milk enriched with PUFA showed a reduction in the concentration of LDL in the blood of rats [ 14 ], and in gilts supplemented with cow’s milk naturally enriched with n-3 and n-6 from 34 days of age until the end of lactation also showed a reduction in LDL for the n-3 and n-6 treatments and improved the performance of weaned piglets [ 15 ]. However, we did not find studies evaluating the effects of providing PUFA-enriched milk on the development of pigs, considering the pig as an animal model for humans.…”
Section: Introductionmentioning
confidence: 99%